New Mutant Amaranth Varieties as a Potential Source of Biologically Active Substances - Jozef Fejér; Ivan Kron; Adriana Eliašová; Daniela Gruľová; Alena Gajdošová; Veronika Lancíková; Andrea Hricová (MDPI AG, 2021)
Amaranth species represent a diverse group of plants. Many of them are a rich source of secondary metabolites with many positive biological effects. Total phenolic, total flavonoid and rutin content, antioxidant activity against superoxide and hydroxyl radicals, FRAP (Ferric-reducing ability of plasma) assay and DPPH (2,2-Diphenyl-1-picrylhydrazyl) radical scavenging assay were determined in ethanol extracts of dried leaves of the new Slovak amaranth varieties 'Pribina' and 'Zobor'. The amount of total phenolic substances ('Pribina' GAE 38.3 mg.g−1 DM and 'Zobor' GAE 26.1 mg.g−1 DM), content of total flavonoids ('Pribina' QE 26.5 mg.g−1 DM and 'Zobor' QE 20.3 mg.g−1 DM) and rutin ('Pribina' 50.8 mg.g−1 DM and 'Zobor' 15.2 mg.g−1 DM) were higher in the variety 'Pribina', compared to the variety 'Zobor'. A statistically higher antioxidant activity against superoxide radical (1.63%·mg−1g−1 DM), hydroxyl radical (3.20%.mg−1g−1 DM), FRAP assay (292.80 µmol.L−1·mg−1.g−1 DM) and DPPH (54.2 ± 1.78 µg.mL−1 DM) were detected in the 'Pribina' variety. Antiradical and antioxidant activities of both extracts showed high positive correlations in relation to the content of total phenolic substances, total flavonoids and rutin. Amaranth is an undemanding crop on specific environmental conditions and is resistant to abiotic and biotic stress.